Toward an Interactive Pedagogical Framework for Islamic Religious Education: Linking Interactive Pedagogy and Islamic Values Through Student Engagement - Ratna Wulandari; Syahidin Syahidin; Agus Fakhruddin; Fahmi Fazar; Mukhlisin Mukhlisin; Rika Lasmini Ritonga; Putu Wia Rosita Dewi; Rosa Fitriani (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Although Game-Based Learning (GBL) has attracted increasing attention in educational research, limited evidence explains how interactive pedagogy can support holistic learning within Islamic Religious Education (IRE). Existing studies have primarily focused on motivation, academic achievement, or technology integration, with less attention to the pedagogical processes through which interactive learning fosters multidimensional student engagement and the contextual enactment of Islamic values. This study investigates the implementation of GBL integrated with the Roaming the Stairs strategy in IRE at an Indonesian Islamic senior high school. Adopting a qualitative case study design, data were collected through classroom observations, in-depth interviews, and document analysis. They were analyzed thematically using an integrated framework comprising Game-Based Learning Theory, Student Engagement Theory, and the Islamic educational philosophy of ta’dīb. The findings reveal that the integrated pedagogical design fostered interconnected behavioral, emotional, cognitive, and social engagement through collaborative, movement-based, and scaffolded learning activities. These learning experiences enabled students to contextualize and demonstrate Islamic values through authentic classroom interactions, indicating that interactive pedagogy functions as a mechanism linking active learning with ethical practice. Based on these findings, the study proposes the Interactive Pedagogical Framework for Islamic Religious Education (IPFIRE), which explains how interactive pedagogy, multidimensional student engagement, and value-based learning operate as complementary dimensions of learner-centered Islamic Religious Education.